Advances in malware and data-driven network security - Gupta, Brij, 1982- (Advances in information security, privacy, and ethics (AISPE) book series., 2022)
"This book describes some of the recent notable advances in threat-detection using machine-learning and artificial-intelligence with a focus on malwares, covering the current trends in ML/statistical approaches to detecting, clustering or classification of cyber-threats extensively"--